Aplikasi vektor beban penentu lokasi kerusakan struktur pada struktur portal rangka ruang - Richard Frans; Yoyong Arfiadi (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Structural health monitoring system is one of the most interesting and important topics in civil engineering. This is because a good structural health monitoring system will increase the reliability of the structure. There are 4 (four) levels in the structural health monitoring system, one of which is damage localization. Damage localization requires an approach or method that can accurately predict the damaged member. One of the methods that is widely applied and proven to give good results for predicting damaged members called damage locating vector (DLV). The DLV method has been applied to several structures, such as plane truss structures, space truss structures, plane frame structures, shear buildings, plane stress elements, thick plate elements and several types of structures. The purpose of this research is to apply DLV method to space frame structures to find out the effectiveness of this method in damage detection. There are three damage scenarios used, two single damage scenarios and one multiple damage scenario. Based on the results obtained, the DLV method can accurately determine the damaged member in the space frame structure for single damage scenarios but in case of multiple damage scenarios, the DLV cannot predict the damaged member due to the values ​​of the end forces and moments of the damaged members are similar to one another.